RANCANG BANGUN APLIKASI KUMPULAN LAGU DAERAH SUMBAWA BERBASIS ANDROID - Shinta Esabella; Yudi Mulyanto; Fahliyah Diani (Hexagon Jurnal Teknik dan Sains, 2020)
In Indonesia there are a lot of distinctive traditional music arts, one of them is Sumbawa traditional music. Sumbawa traditional music is a rich Sumbawa culture with a rhythm represented in temung (type of punch), both temung found in the pond, tambourine and palompong. The traditional music recognition system is one step that can be done in preserving one of the cultures in Sumbawa . The introduction of Sumbawa music can be done using an Android-based application. This study aims to (1) facilitate the Sumbawa native people and people outside Sumbawa to get to know the Sumbawa culture, and (2) preserve the Sumbawa culture which is a cultural heritage. This research uses prototype software development method and is built using Android Studio and SQlite database targeting android version 5.0 (Lollipop). The data collection method uses literature study techniques with Sumbawa Musician sources and uses the beta testing method which is a test conducted by testing the software in terms of functionality. The results of the study are the Android-Based Sumbawa Regional Song Collection Application that can be accessed through the Play Store equipped with select songs, information and about the application so that it can contribute to the music culture of Sumbawa (Samawa Songs).